2008
DOI: 10.1681/asn.2007090983
|View full text |Cite
|
Sign up to set email alerts
|

Resolved

Abstract: Obesity is the epidemic of the 21st century. Despite the fact that obesity is known to have major health consequences in the general population, an increasing number of large-scale epidemiological studies indicate an inverse association between increasing body mass index and mortality in dialysis patients. Here it is argued pro and con that epidemiological data derived from the healthy general population may or may be not applicable to conditions such as end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 47 publications
(15 reference statements)
1
36
0
1
Order By: Relevance
“…26 However, it remains unclear which type of nutritional store, in particular fat or muscle, is more protective and the extent to which a lower body mass is detrimental in patients with CKD. 29 For personal use. Mass reproduce only with permission from Mayo Clinic Proceedings a .…”
Section: Discussionmentioning
confidence: 99%
“…26 However, it remains unclear which type of nutritional store, in particular fat or muscle, is more protective and the extent to which a lower body mass is detrimental in patients with CKD. 29 For personal use. Mass reproduce only with permission from Mayo Clinic Proceedings a .…”
Section: Discussionmentioning
confidence: 99%
“…Whether that finding is associated with lower body mass index, triglycerides, and energy intake in those patients needs to be explored. Given the strong epidemiologic data already showing lower survival with declining body mass index and lower serum lipids in maintenance dialysis patients (25)(26)(27), estimation of the health effects of silent peritonitis episodes should take the harmful consequences of deficient energy stores into account. However, we could not draw a conclusion about the relationship between silent peritonitis and malnutrition, given that lean body mass and DPI did not really vary between the silent and non-silent peritonitis groups.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancy exists even regarding the upper BMI limit for survival advantage, with some studies reporting a positive effect even at BMI values .35 kg/m 2 and others indicating an upper limit of 25 kg/m 2 (7,8). Postulated reasons for improved survival with high BMI include potential benefits of adipose tissue per se, for example as a source of TNF-a-soluble receptors and lipoproteins that counteract the effects of TNF-a itself or the inflammatory effects of circulating endotoxins (8-10) or as a vital energy source in undernourished patients (10). In health, aging is associated with loss of muscle mass in the range of 2-4 kg over 10 years (11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with surrogate markers of FTM and LTM suggest a dominant protective role of LTM over FTM (7,17,19,20). However, other studies concluded that survival is dependent more on FTM than LTM (10,21). Recently, multifrequency bioimpedance spectroscopy (MF-BIS) devices have been introduced to assess body composition in HD patients.…”
Section: Introductionmentioning
confidence: 99%